2019
DOI: 10.1001/jamasurg.2019.0151
|View full text |Cite|
|
Sign up to set email alerts
|

Use of Combat Casualty Care Data to Assess the US Military Trauma System During the Afghanistan and Iraq Conflicts, 2001-2017

Abstract: IMPORTANCE Although the Afghanistan and Iraq conflicts have the lowest US case-fatality rates in history, no comprehensive assessment of combat casualty care statistics, major interventions, or risk factors has been reported to date after 16 years of conflict. OBJECTIVES To analyze trends in overall combat casualty statistics, to assess aggregate measures of injury and interventions, and to simulate how mortality rates would have changed had the interventions not occurred. DESIGN, SETTING, AND PARTICIPANTS Ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
153
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 186 publications
(162 citation statements)
references
References 41 publications
2
153
0
7
Order By: Relevance
“…Furthermore, a secondary analysis of the Pragmatic Randomized Optimal Platelet and Plasma Ratios (PROPPR) trial that compared outcomes of trauma patients who were resuscitated with two different blood product ratios found a 5% increase in mortality for every minute that blood products were not provided to a trauma patient after the massive transfusion protocol (MTP) had been activated . Lastly, two recent studies of military casualties revealed that the prompt transfusion of blood products resulted in impressive reductions in mortality . These findings underscore the importance of having blood products available early in the resuscitation of massively bleeding trauma patients.…”
Section: Modern Emergency Resuscitation Strategies For Massively Bleementioning
confidence: 90%
“…Furthermore, a secondary analysis of the Pragmatic Randomized Optimal Platelet and Plasma Ratios (PROPPR) trial that compared outcomes of trauma patients who were resuscitated with two different blood product ratios found a 5% increase in mortality for every minute that blood products were not provided to a trauma patient after the massive transfusion protocol (MTP) had been activated . Lastly, two recent studies of military casualties revealed that the prompt transfusion of blood products resulted in impressive reductions in mortality . These findings underscore the importance of having blood products available early in the resuscitation of massively bleeding trauma patients.…”
Section: Modern Emergency Resuscitation Strategies For Massively Bleementioning
confidence: 90%
“…Moreover, the recent achievements of military trauma systems in reducing battlefield mortality have drawn upon many technological advances, including the use of blood products in far forward positions, the reliance on airpower for rapid evacuation of casualties, and the development of sophisticated trauma registries that have allowed for the identification of suboptimal care and real-time improvements. A recent analysis by Howell et al (2019), reviewing U.S. servicemember casualties in Iraq and Afghanistan, found that improvements in blood product availability, tourniquet use, and reduction in pre-hospital transport times accounted for nearly half of the reduction in case fatality in those conflicts [5]. Some observers have raised concerns that, in the absence of such advances, echeloning care may be counterproductive or even harmful if such echelons delay rather than expedite access to appropriate care.…”
Section: Discussionmentioning
confidence: 99%
“…In many ways, this pathway represented a marked departure from "business as usual" for humanitarian trauma care in wartime. Although echelons of care are well-described in war surgery literature, they are most commonly associated with western militaries, having been deployed in military responses in Vietnam, Israel, and the Falkland Islands in the 1970s and 1980s through Afghanistan and Iraq more recently [4,5]. These military evacuation chains provided first aid near the point of injury, transport of the critically wounded, and surgical care for combatants and, to varying degrees, injured civilians.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 This contemporary JTTS resulted in a steady decrease in combat case fatality rates despite increasingly severe injuries sustained by wounded troops. [12][13][14] The most recent analysis of data documents that between 2001 and 2017, the combat case fatality rates (defined as the number of troops killed in action plus those who died of wounds divided by the sum of those killed in action plus those wounded in action) decreased in Afghanistan from 20% to 8.6%; in Iraq it went from 20.4% to 10% 15 (Fig. 2).…”
Section: Punctuated Equilibrium Theory and The Military Health Systemmentioning
confidence: 99%